14C-Dating of the Late Bronze Age City of Hala Sultan Tekke, Cyprus: Status Report. Issue 5 (October 2019) - Wild, Eva M; Fischer, Peter M; Steier, Peter; Bürge, Teresa
ABSTRACT: Hala Sultan Tekke is a large Bronze Age city located on the southeastern littoral of Cyprus. The city flourished from approximately 1650 BC to 1150 BC according to the archaeological evidence. Since 2010, Swedish excavations have exposed four new city quarters (CQ1–4) with three occupational phases, the 14 C dating of which is of highest importance also for other contemporaneous cultures. The finds demonstrate vast intercultural connections in the Mediterranean and even with southern Scandinavia. In 2014, roughly 500 m to the east of CQ1, one of the richest cemeteries on the island was discovered. According to the archaeological evidence, the finds from the city date mainly to the 13th and 12th centuries BC. However, many of the wealthy tombs and the offering pits from the cemetery are considerably older with the oldest finds dating to the 16th century BC. This raises the question where the city quarters belonging to the oldest finds from the cemetery are situated. The radiocarbon ( 14 C) dates from Hala Sultan Tekke have much influence on the dating of related sites because of numerous imports from a vast area. We present here new 14 C data obtained in the course of the current excavations, which add to sets of already existing data.